Classroom Application of Micro Teaching : An Analysis of Students’ Perspectives - Yuliani, Sri (Program Studi Pendidikan Bahasa Inggris FKIP UIR, 2018)
Microteaching is a practical event which is very beneficial for candidate teachers to have real environment of teaching. The candidate teachers get big chances to implement their experience in teaching. The students’ perfectives are crucial for promoting teacher education programs’ outcomes. This study aimed at investigating the students’ views of thirty students from the English Language Education Program of FKIP-UIR. A combination of quantitative and qualitative techniques used in gathering the data. Mainly, a questionnaire and a focus group interview were used as the main tools for data collection. The findings revealed that the entire sample of student has stated that they were having their own perspectives towards Microteaching and their opinion during microteaching sessions provides a scope to enhance their teaching skills for real teaching sessions. Based on the findings, these candidate teachers were glad to have real teaching session during microteaching class